Website Agenda Kegiatan Pada Ombudsman RI Perwakilan Sumatera Selatan - Afny Istiqomah; Nia Oktaviani (CV. Multi Kreasi Media, 2026)
Manual management of activity schedules has the potential to cause various problems, including delays in information dissemination, difficulties in data retrieval, limited integration between departments, and the risk of data loss. This situation also occurs at the Representative Office of the Ombudsman of the Republic of Indonesia in South Sumatra, which still relies on simple media to manage activity schedules and assignment letters. This community service project aimed to develop a web-based Activity Agenda Website capable of supporting the recording, management, and dissemination of activity information in an effective, structured, and integrated manner. The system was developed using the Waterfall methodology, which consists of the requirements analysis, system design, implementation, testing, and maintenance phases. The implementation employed the Laravel framework with the Blade Template engine, while functional testing was conducted using the Black Box Testing method to ensure that all system features operated according to user requirements. The results of this community service project indicate that the developed website is capable of managing activity agenda data, assignment letters, and user management in a centralized and real-time manner. The system also facilitates the recording, searching, updating, and dissemination of information, thereby improving administrative efficiency, coordination among employees, and the quality of activity documentation within the South Sumatra Representative Office of the Ombudsman of the Republic of Indonesia. Therefore, the proposed Activity Agenda Website provides an effective solution for supporting a more modern, integrated, and well-documented administrative governance system.